The Influence of Transformational Leadership and Organizational Culture on Teacher Performance in Formal Schools in the Scope of Islamic Boarding Schools in Bangil District Pasuruan - Muhammad Rafly Syahlan Nizammuddin; Mustaji; I Ketut Atmaja Johny Artha; Amrozi Khamidi (CV. Edujavare Publishing, 2026)
This study aims to determine the influence of transformational leadership and organizational culture on teacher performance in formal schools within Islamic boarding schools (pesantren) throughout Bangil District. The data collection method used was questionnaire documentation. The population in this study was all teachers at two Islamic boarding schools: Roudlotul Aqoidi Islamic Boarding School and Darut Tauhid Islamic Boarding School, which have formal junior high schools. The sampling method used was probability sampling, where all members of the population had the opportunity to be selected. Since the population size was less than 100, the sampling requirement was to take all 31 members of the population. The data analysis techniques used in this study included validity testing, reliability testing, multiple regression equation testing, and hypothesis testing. The results of the study indicate that transformational leadership and organizational culture significantly influence teacher performance in formal schools within Islamic boarding schools throughout Bangil District, amounting to 74.4%.